2016
DOI: 10.1111/joor.12417
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mucosal pain in patients with partial removable dental prostheses

Abstract: The aim of this study was to investigate factors associated with mucosal pain in patients with partial removable dental prostheses (PRDPs). In this hospital-based cross-sectional study, 333 patients wearing 500 PRDPs (mean age 71·4 years, men 33·3%) were consecutively recruited from prosthetic clinic of a dental hospital in Japan. Subjects rated pain intensity and frequency of denture-bearing mucosa. An examiner recorded age, gender and systemic diseases as well as dental, mucosa, denture, sensory, behavioural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Among the factors included in our SEM, the direct effect of oral dryness on the CA score was the greatest, which is in line with previous findings . In addition, oral dryness was also previously identified as a risk factor for mucosal pain . Therefore, from a clinical perspective, both mucosal pain and oral dryness should be considered in treatment with PRDPs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the factors included in our SEM, the direct effect of oral dryness on the CA score was the greatest, which is in line with previous findings . In addition, oral dryness was also previously identified as a risk factor for mucosal pain . Therefore, from a clinical perspective, both mucosal pain and oral dryness should be considered in treatment with PRDPs.…”
Section: Discussionsupporting
confidence: 90%
“…Mucosal pain is one of the most common complaints in patients with removable dental prostheses (RDPs) . In cross‐sectional studies, 20%‐50% of patients with RDPs experienced mucosal pain when using dentures . Mucosal pain is noxious stimulation of the denture bearing mucosa while occluding and chewing with dentures; thus, mucosal pain could be a cause of masticatory function impairment.…”
Section: Introductionmentioning
confidence: 99%
“…They found that this group presented significantly more masseter muscle EMG activity that the control group (i.e., denture wearers without pain) during rest, and suggested that identifying AB is of great importance for the success of subsequent treatment of denture wearers. 27 Similarly, Kumagai et al 28 showed that AB, as well as other factors (such as age, number of missing teeth, mucosal condition, mucosal damage, bone prominence), is an independent predictor of intensity and frequency of mucosal pain in the denture-bearing area of patients with partial removable dental prostheses. It would be of interest to investigate whether AB is related to mucosal pain in implant-supported RP wearers, and if so, if this mechanism can be used in treatment planning following the aversive conditioning paradigm.…”
Section: Discussionmentioning
confidence: 98%
“…Denture sores were another major source of maintenance needs in the present investigation. Studies have shown that interim dentures are associated with increased mucosal pain and, accordingly, with reduced chewing ability [18,19]. An effort should therefore be made to achieve secure and pain-free seating of the denture so that good masticatory function will be ensured.…”
Section: Oral-health Implicationsmentioning
confidence: 99%